The Impact of Refutation Texts in Scientific Conception: Meta-analysis - Amiruddin, Mohd Zaidi Bin; Samsudin, Achmad; Suhandi, Andi; Kaniawati, Ida; COŞTU, Bayram (Jurnal Pendidikan MIPA, 2025)
This research aimed to analyze the role and impact of refutational text on student conceptions and learning outcomes. Utilizing meta-analysis methods, this study sourced articles from the Scopus and Web of Science databases, covering publications from 2001 to 2023. The article selection process adhered to the PRISMA technique, implemented systematically in several stages to ensure rigor and transparency. The meta-analysis used the random-effects model to account for variability among studies, offering a more generalized understanding of the effects of refutational text across different contexts and populations. The results were synthesized through a Forest plot, revealing a standard mean difference with a P value of <0.01, indicating a statistically significant effect of refutational text on students’ conceptions. This suggests that the use of refutational text substantially influences learning, particularly in addressing misconceptions. Additionally, the study highlighted that while the potential for applying refutational texts in Indonesia is promising, the number of global and internationally indexed publications on this topic remains limited. This lack of extensive research limits the broader application of refutational text in educational contexts. However, the findings suggest that refutational text holds significant promise for science education, especially for topics where students commonly hold misconceptions about difficult concepts. Further research is recommended to explore its full potential and to encourage the publication and wider application of refutation texts in science education.       Keywords: refutation text, meta-analysis, conception, conceptual change.